Gamification in EFL Classroom: Results of Implementation and Teachers’ Point of View - Permana, I Gede Yoga; Rismadewi, Ni Wayan Monik; Putra, Nyoman Canestra Adi (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
The present study aimed to investigate the implementation of gamification on students' English proficiency and to assess teachers' reactions to its integration into the EFL classroom. This research employed a mixed-methods approach, utilizing a pretest-posttest experimental design complemented by semi-structured interviews. The study involved forty-three elementary students and two English teachers in one private school in Singaraja, Bali. In collecting the data, this study used multiple choice test, performance-based test and interview guide. The study was also incorporating rubric for assessing students speaking and writing skills. The results of the study found that the posttest score of overall English (M= 73.70, Std=7.812) was higher than the pretest score (M= 70.53, Std=8.174). The results of paired t test also confirmed that there was significant difference of mean score between pretest and posttest (Sig<.05). During the interview, the teachers mentioned that the students were engaged, active and motivated during learning process. The study concluded that gamification significantly influenced students' English skills, eliciting a positive response from teachers towards its implementation in the classroom. These findings contribute significantly to the broader discourse on innovative teaching methodologies and their favorable effects on student engagement and learning outcomes.